Acute interactions between intestinal sugar and calcium transport in vitro - Phuntila Tharabenjasin (2018)
Fructose consumption by Americans has increased markedly, whereas Ca2+intake has decreased below recommended levels. Because fructose metabolism decreases enterocyte ATP concentrations, we tested the hypothesis that luminal fructose acutely reduces active, diet-inducible Ca2+transport in the small intestine. We confirmed that the decrease in ATP concentrations was indeed greater in fructose- compared with glucose-incubated mucosal homogenates from wild-type and was prevented in fructose-incubated homogenates from ketohexokinase (KHK)-/-mice. We then induced active Ca2+transport by chronically feeding wild-type, fructose transporter glucose transporter 5 (GLUT5)-/-, as well as KHK-/-mice a low Ca2+diet and measured transepithelial Ca2+transport in everted duodenal sacs incubated in solutions containing glucose, fructose, or their nonmetabolizable analogs. The diet-induced increase in active Ca2+transport was proportional to dramatic increases in expression of the Ca2+-selective channel transient receptor potential vanilloid family calcium channel 6 as well as of the Ca2+-binding protein 9k (CaBP9k) but not that of the voltage-dependent L-type channel Ca(v)1.3. Crypt-villus distribution of CaBP9k seems heterogeneous, but low Ca2+diets induce expression in more cells. In contrast, KHK distribution is homogeneous, suggesting that fructose metabolism can occur in all enterocytes. Diet-induced Ca2+transport was not enhanced by addition of the enterocyte fuel glutamine and was always greater in sacs of wild-type, GLUT5-/-, and KHK-/-mice incubated with fructose or nonmetabolizable sugars than those incubated with glucose. Thus duodenal Ca2+transport is not affected by fructose and enterocyte ATP concentrations but instead may decrease with glucose metabolism, as Ca2+transport remains high with 3-O-methylglucose that is also transported by sodium-glucose cotransporter 1 but cannot be metabolized. © 2014 the American Physiological Society.